Influência da escoria de aciaria LD no desempenho de concretos com baixo consumo de cimento - Tainá Varela de Melo (2020)
The concrete production, the most consumed building material in the world, is associated with a high consumption of natural resources. In this scenario, the search for alternative materials that replace natural aggregates and Portland cement becomes an important issue in the civil construction scenario, driving researchers in the search for solutions. On the other hand, steel production generates slags whose destination is often inadequate. However, these by-products because they have high amounts of Ca, Si and Fe in their composition, in the form of silicates and oxides, have similarities with the raw materials consumed in the production of concretes, such as supplementary cementitious materials and aggregates. Thus, the slag has great potential for application in cementitious matrices, provided that criteria of mechanical performance and durability are met. The present work proposes to produce and study concretes with low cement consumption with the use of BOFS, based on methodology described in the literature, and to analyze their performance with the use of this by-product as coarse and fine aggregates and supplementary cementitious material. The study has a sustainability and efficiency approach, since concretes are developed with slag consumption of up to 96.5% in volume of solids and assessment of their competence through assessments of physical, chemical, mechanical and durability parameters. Two traits were studied: one with conventional aggregates and the other with slag aggregates, both with a cement consumption of less than 90 kg / m³ and with the same amount of LD slag fines as supplementary cementitious material. The results indicated that the mixture with steel slag aggregates stood out when reaching a cement intensity of 2.47 kg / m³ / MPa, while the mixture with natural aggregates reached 3.51 kg / m³ / MPa. The performance of these concretes in relation to the parameters of durability and microstructural characteristics corroborated with the physical and mechanical tests, inferring a good behavior towards harmful agents. The eco-efficiency assessment consolidated that the use of the concrete proposed in this work can imply cost reduction, high consumption of recycled material and reduction of impacts caused by the consumption of natural aggregates and cement.